Recent sedimentological interpretations in the Avalon terrane of the Boston Basin, Massachusetts - Socci, Anthony; Smith, Geoffrey (Atlantic Geology, 1987)
The depositional history of the Boston Basin remains somewhat enigmatic and controversial despite nearly over a century of research. Resolution of the basin's geologic history has remained formidable and complex due. In part, to attempts to work within the existing stratigraphy which often carried with it historic interpretations, many of which went uncontested. More importantly however, our knowledge of depositional systems and mechanisms has Increased significantly over this span of time. Reinterpretatlons In light of these advances were not only Inevitable but neccessary. As a consequence of the circumstances described above, our reinvestigation into the depositional history of the Boston Basin succession, principally the Boston Bay Group, has centered on recognizing, measuring, and coding a suite of facies whose textures In many Instances can be closely linked to specific depositional mechanisms responsible for the emplacement of the facies in question. From this facies analysis a preliminary depositional model for the Boston Basin has begun to emerge. It appears that the Boston Basin originated as a rifted successor, or arc-related basin either just prior to the closure of the Cadomlan Ocean or during the opening of Iapetus. The early history of the basin Is marked by the presence of a suite of bimodal volcanics In the form of water-lain tuffs, dikes, sills, and flows, and coarse debris flows. Geochemlcal markers suggest that the basin was In contact with the open ocean very early In its history. The next stage In the evolution of the Boston Basin was marked by the development of a rapidly prograding submarine elope/fan succession. The slope/fan Betting appears to have been characterized by the deposition of ice frontal and/or ice-rafted dlamictons which periodically overloaded the slope Initiating sediment gravity flows which reworked and redistributed sediment downslope. During periods of more equable climate and/or tectonic quiescence, blankets of fine sand and mud were deposited. There Is no evidence of a shelf or shelf-type deposits during this time. The last stage in the evolution of the basin was the appearance of shelf sediments such as quartz and calcareous sands, and muds with abundant organic matter and shelled organisms. There Is also evidence for climatic warming which is suggested to have been brought about by a tectonlcally-forced rise In eustatic sea-level.